A Gender-Based and Quasi-Experimental Study of the Catastrophic and Impoverishing Health-Care Expenditures in Mexican Households with Elderly Members, 2000-2020. Issue 1 (31st December 2023) - Serván-Mori, Edson; Orozco-Núñez, Emanuel; Guerrero-López, Carlos M.; Miranda, J. Jaime; Jan, Stephen; Downey, Laura; Feeny, Emma; Heredia-Pi, Ileana; Flamand, Laura; Nigenda, Gustavo; Norton, Robyn; Lozano, Rafael
ABSTRACT: Latin America has experienced a rise in noncommunicable diseases (NCDs) which is having repercussions on the structuring of healthcare delivery and social protection for vulnerable populations. We examined catastrophic (CHE) and excessive (EHE, impoverishing and/or catastrophic) health care expenditures in Mexican households with and without elderly members (≥65 years), by gender of head of the households, during 2000–2020. We analyzed pooled cross-sectional data for 380, 509 households from eleven rounds of the National Household Income and Expenditure Survey. Male- and female-headed households (MHHs and FHHs) were matched using propensity scores to control for gender bias in systematic differences regarding care-seeking (demand for healthcare) preferences. Adjusted probabilities of positive health expenditures, CHE and EHE were estimated using probit and two-stage probit models, respectively. Quintiles of EHE by state among FHHs with elderly members were also mapped. CHE and EHE were greater among FHHs than among MHHs (4.7% vs 3.9% and 5.5% vs 4.6%), and greater in FHHs with elderly members (5.8% vs 4.9% and 6.9% vs 5.8%). EHE in FHHs with elderly members varied geographically from 3.9% to 9.1%, being greater in less developed eastern, north-central and southeastern states. Compared with MHHs, FHHs face greater risks of CHE and EHE. This vulnerability is exacerbated in FHHs with elderly members, because of gender intersectional vulnerability. The present context, marked by a growing burden of NCDs and inequities amplified by COVID-19, makes key interlinkages across multiple Sustainable Development Goals (SDGs) apparent, and calls for urgent measures that strengthen social protection in health.